Analisis Nilai Tambah Usaha Pengolahan Kopi Green Beans dan Kopi Bubuk di Begawan Ringgit - Muhammad Faiz Rizkiawan; Indra Tjahaja; Dona Wahyuning Laily (Universitas Batangahari Jambi, 2023)
The purpose of this study was to determine the production process of the green coffee bean and ground coffee processing business, to analyze the value of income from the coffee bean and coffee powder processing business, and to analyze the amount of added value from the green coffee bean processing business and ground coffee at Begawan Ringgit. This study uses the case study method, this study focuses on the hayami formula to analyze the income and added value of the mung bean and coffee powder business in Begawan Ringgit. Respondents in this study were the owners and employees of the Begawan Ringgit coffee business. Quantitative analysis in the form of analysis of income and added value. The results of this study indicate that the value of income obtained from the mung bean processing business is Rp. 5,275,400/production and the income derived from the robusta coffee processing business is Rp. 2,775,400/production. Meanwhile, the income obtained from the green bean processing business is IDR 85,275,400/production and Arabica ground coffee is IDR 5,275,400/production. The added value of arabica green beans is greater than the added value of robusta green beans. The added value of arabica green beans is IDR 23,700 (59.25%), while the added value of robusta green beans is IDR 20,805 (65.01%). The added value of robusta ground coffee and arabica ground coffee have the same added value of Rp. 18,000 (30%) for robusta ground coffee and Rp. 18,000 (22.5%) for arabica ground coffee